Hemoblastosis. Acute Leukeosis (Eurasian Medical Research Periodical, 2024)
Hemoblastoses are tumors arising from hematopoietic cells. According to world statistics, leukemia is observed in 3.3-4.7 cases out of 100,000 children, children under 15 years of age. 40-46% of them correspond to children aged 2-6 years